Long-Term Effects of Child Early Surgical Ventricular Septal Defect Repair on Maternal Stress - Jennifer Gerlach; Elena S. Decker; Anne-Christine Plank; Stefan Mestermann; Ariawan Purbojo; Robert A. Cesnjevar; Oliver Kratz; Anna Eichler (MDPI AG, 2023)
The ventricular septal defect (VSD) represents the most common congenital heart defect (CHD). The diagnosis of and cardiac surgery for their child's VSD are highly stressful experiences for parents; especially mothers, who are at risk of developing long-lasting stress-related symptoms. This study examined long-term alterations in maternal stress including self-reported psychological and biophysiological stress levels in a case-control design. We investigated 24 mothers of children with an isolated, surgically corrected VSD compared to non-affected controls. Maternal self-reports on psychopathology, everyday stress, parenting stress and hair cortisol concentrations (HCC) were measured during children's primary school age (6-9 years, t1) and early adolescence (10-14 years, t2). In maternal self-reports, psychopathology and stress symptoms in the VSD-group and controls were comparable at t1, whereas at t2, mothers in the VSD-group even showed a decrease in psychopathology. Maternal HCC levels in the VSD-group were significantly lower (hypocortisolism) than HCC levels of controls at t1. This effect was no longer observed at t2 reflecting an approximation of HCC levels in the VSD-group to controls' levels. This study highlights the potential for improved stress hormone balance and psychological well-being in mothers following their child's surgical VSD repair. However, the need for parent-centered interventions is discussed, particularly during peri-operative phases and in early child developmental stages.